Development of Inclusion Complexes With Relative Humidity Responsive Capacity as Novel Antifungal Agents for Active Food Packaging - Muñoz-Shugulí, Cristina; Rodríguez-Mercado, Francisco; Mascayano, Carolina; Herrera, Andrea; Bruna, Julio E.; Guarda, Abel; Galotto, María J. (Frontiers in Nutrition, 2022)
The use of responsive packaging materials is a novel strategy to keep the food safety. On the other hand, beta-cyclodextrin (β-CD) could act as relative humidity-responsive nanoparticle. This fact in turn would allow the use of the inclusion complexes based on β-CD as responsive agents to develop polymeric materials for active food packaging. In this research, different β-CD inclusion complexes were development and the effect of relative humidity on allyl isothiocyanate (AITC) release from the inclusion complexes was deeply studied. Two different β-CD:AITC inclusion complexes (2:1 and 1:1 molar ratio) were obtained by co-precipitation method. Entrapment efficiency was determined by gas chromatography and inclusion complexes were characterized through thermal, structural and physicochemical techniques. Antifungal capacity of inclusion complexes was determined in a headspace system. Furthermore, AITC release from inclusion complexes to headspace was evaluated by gas chromatography and it was related with molecular dynamic studies. The entrapment efficiency of inclusion complexes was up to 60 %. Two coexisting structures were proposed for inclusion complexes through spectroscopic analyses. The water sorption capacity of inclusion complexes depended on relative humidity, and they exhibited fungicide properties against Botrytis cinerea. Furthermore, the AITC release to headspace occurred in three stages, which were related with changes in β-CD conformational structure by water sorption and the presence of the different coexisting structures. Additionally, a strong influence of relative humidity on AITC release was evidenced. These findings demonstrate that β-CD:AITC inclusion complexes could be used as potential antifungal agents for the design of food packaging materials, whose activity would be able to respond to relative humidity changes.